Cancer mortality among Colombian and foreign populations over a 15-year period - Diana M. Hernandez; Amr S. Soliman; Almira G.C. Lewis; Isabel C. Garcés-Palacio (Elsevier, 2024)
Purpose: We aimed to compare cancer mortality among foreign- and Colombian populations in Colombia during the period of 2006-2020. Methods: This retrospective study utilized vital statistics from the Colombian National Department of Statistics (DANE). The dataset included variables such as age group, sex, country of permanent residency, insurance, education level, marital status, ethnicity, and cause of death. The population data to calculate rates was obtained from the Colombian census and the United Nations. Crude and adjusted rates as well as proportional mortality rates were calculated. Results: A total of 561,932 cancer deaths occurred in Colombia from 2006 to 2020. The foreign population (country of permanent residency different to Colombia) had a lower crude cancer mortality rate (31.1 per 100,000 inhabitants) than the Colombian population (81.9 per 100,000 inhabitants). However, the age-adjusted cancer mortality rate among the foreign population was 253.6 per 100,000, compared to 86.1 per 100,000 among the Colombian population. The proportional cancer mortality was 10.4 % among foreign population compared to 17.4 % among Colombian population. Conclusions: The proportional cancer mortality shows that the proportion of cancer-related deaths is greater among the Colombian population compared to the immigrant population. However, immigrants in Colombia have a higher age-adjusted cancer mortality rate than Colombians, indicating that immigrants have worse cancer outcomes than the Colombians even though the immigrant population is younger. This is likely due to the frequent barriers that immigrants encounter in accessing health care in Colombia. Future research needs to focus on access to care for the immigrant population by investigating cancer-related risk factors among immigrants and addressing their barriers to cancer prevention and treatment.